Rho family GTPases: key players in neuronal development, neuronal survival, and neurodegeneration - Stankiewicz, Trisha R.; Linseman, Daniel A. (Frontiers in Cellular Neuroscience, 2014)
The Rho family of GTPases belongs to the Ras superfamily of low molecular weight (~21 kDa) guanine nucleotide binding proteins. The most extensively studied members are RhoA, Rac1, and Cdc42. In the last few decades, studies have demonstrated that Rho family GTPases are important regulatory molecules that link surface receptors to the organization of the actin and microtubule cytoskeletons. Indeed, Rho GTPases mediate many diverse critical cellular processes, such as gene transcription, cell-cell adhesion, and cell cycle progression. However, Rho GTPases also play an essential role in regulating neuronal morphology. In particular, Rho GTPases regulate dendritic arborization, spine morphogenesis, growth cone development, and axon guidance. In addition, more recent efforts have underscored an important function for Rho GTPases in regulating neuronal survival and death. Interestingly, Rho GTPases can exert either a pro-survival or pro-death signal in neurons depending upon both the cell type and neurotoxic insult involved. This review summarizes key findings delineating the involvement of Rho GTPases and their effectors in the regulation of neuronal survival and death. Collectively, these results suggest that dysregulation of Rho family GTPases may potentially underscore the etiology of some forms of neurodegenerative disease such as amyotrophic lateral sclerosis (ALS).